2021
DOI: 10.1186/s40364-021-00326-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection and clinical significance of circulating tumor cells in colorectal cancer

Abstract: Histopathological examination (biopsy) is the “gold standard” for the diagnosis of colorectal cancer (CRC). However, biopsy is an invasive method, and due to the temporal and spatial heterogeneity of the tumor, a single biopsy cannot reveal the comprehensive biological characteristics and dynamic changes of the tumor. Therefore, there is a need for new biomarkers to improve CRC diagnosis and to monitor and treat CRC patients. Numerous studies have shown that “liquid biopsy” is a promising minimally invasive me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 132 publications
(174 reference statements)
0
25
0
Order By: Relevance
“…Some literature used ctDNA to monitor disease progression in colorectal cancer after early and medium-term, although the specificity was high (93%), its sensitivity was only 27% [ 36 ]. Circulating tumor cells (CTCs) are rare cancer cells that shed from tumor cells and remain in the circulating bloodstream, and are thought to be the "seeds" that initiate cancer progression and metastasis [ 14 ], At present, a number of clinical studies have confirmed that the existence of CTCs is closely related to recurrence and metastasis. Uen et al [ 25 ] believed that early recurrence after stage I-III CRC was closely related to the persistent presence of CTC in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some literature used ctDNA to monitor disease progression in colorectal cancer after early and medium-term, although the specificity was high (93%), its sensitivity was only 27% [ 36 ]. Circulating tumor cells (CTCs) are rare cancer cells that shed from tumor cells and remain in the circulating bloodstream, and are thought to be the "seeds" that initiate cancer progression and metastasis [ 14 ], At present, a number of clinical studies have confirmed that the existence of CTCs is closely related to recurrence and metastasis. Uen et al [ 25 ] believed that early recurrence after stage I-III CRC was closely related to the persistent presence of CTC in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…Although the sensitivity and specificity of PET-CT in monitoring postoperative recurrence and metastasis of CRC are relatively high [ 9 ], PET/CT examination is expensive and has high requirements for imaging physicians, which affects its clinical promotion and use. Circulating tumor cells (CTCs) are tumor cells shed from primary or secondary tumor masses that circulate in the bloodstream [ 10 ], In the past, CTCs was often used in the early diagnosis, monitoring of recurrence and metastasis, prognosis and efficacy evaluation of malignant tumors such as lung cancer [ 11 ], breast cancer [ 12 ], prostate cancer [ 13 ] and colorectal cancer [ 14 ] and so on. However, there has been no unified view of the value of CTCs in postoperative recurrence and metastasis of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…CTCs are a promising biomarker for early disease diagnosis, treatment response and disease progression evaluation, recurrence monitoring, and therapeutic target identification for drug development [118]. Detection of CTCs has been widely used in the diagnosis of early and metastatic cancers (Table 1).…”
Section: Clinical Applications Of Ctcsmentioning
confidence: 99%
“…As such, liquid biopsies set ground for a rapid, noninvasive way for cancer diagnosis and prognostic markers [ 70 ]. Currently, liquid biopsies have gained clinical application for metastatic breast cancer [ 71 ], small cell lung cancer [ 72 ], prostate [ 73 ] and colorectal cancer [ 74 ] in the context of tumor diagnosis and longitudinal monitoring of therapy responses in both primary and metastasized tumors. Specifically, it has been shown that CTC count in peripheral blood correlates to therapy response.…”
Section: Introductionmentioning
confidence: 99%